A survey of 222Rn concentrations in dwellings of the town of Metsovo in North-western Greece - Ioannides, K. G.; Stamoulis, K. C.; Papachristodoulou, C. A. (HNPS Advances in Nuclear Physics, 2019)
A radon survey has been carried out of indoor radon concentrations in dwellings ocated in the town of Metsovo, in north-western Greece. To measure indoor radon ioncentrations, CR-39 detectors were installed in randomly selected houses and were exposed :or about 3 months, during summer and winter. Also gamma spectroscopy measurements of he soil’s radium content were performed. The indoor radon concentration levels varied from [7.6 to 750.4 Bq m-3, while the radium concentration of soil varied from 4.9 to 97.1 Bq m"3. Seasonal variation of the radon levels and the influence of house features and sou are liscussed.